Frantice.net - Réseau de chercheurs en technologies de l'information et de la communication pour l'enseignement; Agence universitaire de la francophonie; Université de Limoges (Res@tice et l'Université de Limoges, 2010)
Focus on the uses of modern technology in education, with an emphasis on international cooperation in development.
Keywords: High technology and education; Internet in education; Telecommunication in education; Education : International cooperation; Education, Special Topics